P009 A RARE CASE OF A GASTRIC ABSCESS FISTULIZING TO THE DUODENUM IN CROHN'S DISEASE. (18th January 2018) - Zeddun, Steven; Pavle, Alexis; Khan, Ali; Lambdin, Jacob; Borum, Marie L
Abstract: Introduction: Clinically significant gastroduodenal involvement of Crohn's disease (CD) is rare, affecting only 0.5–4% of CD patients. Gastric abscesses from CD are not well-documented in the existing literature. In this report, we present a rare case of CD complicated by a gastric abscess with fistulization to the duodenum. Case: A 32-year-old male with CD complicated by perianal and enterocutaneous fistulas s/p right hemicolectomy and ileostomy presented with two weeks of progressive abdominal pain and purulent drainage from his ileostomy site. Physical exam was notable for generalized abdominal tenderness. Labs were pertinent for WBC 15 × 103/mm3, platelets 646 × 103/mm3, Na 124 mmol/L, and CRP 67 mg/L. He was started on ciprofloxacin and metronidazole. CT revealed a gastric antral stricture with two small collections or fistula in the ventral gastric wall. EGD showed a soft subepithelial lesion with an overlying 3–4 mm white-based ulcer located in the gastric antrum adjacent to the pylorus which produced a large amount of purulent drainage after biopsy (Figure 1). Purulent material was also seen actively draining into the duodenal bulb from an unvisualized source, likely a fistula from the antral abscess (Figure 2). Discussion: Our case presented with a gastric abscess complicated by an antral-duodenal fistula draining purulent material. The antral abscess was confirmed endoscopically with biopsy enhancing drainage. The recommended treatment for intramural gastric abscesses has generally been surgical drainage in combination with antibiotics. Follow-up imaging will determine if further intervention, endoscopic or surgical, is necessary in this patient. This is the first case of a gastric abscess from Crohn's disease that had fistulized to the duodenum resulting in spontaneous drainage that was enhanced by endoscopic intervention. Awareness of this rare complication and therapeutic options is important to optimize clinical outcomes.